Does Clerkship Rotation Sequence Affect Performance on National Board of Medical Examiners (NBME) Clinical Subject Examinations and United States Medical Licensing Examination (USMLE) Step 2 Clinical Knowledge (CK) Examination? - Gao, Hong; Askew, Kim; Violato, Claudio; Manthey, David; Burns, Cynthia; Vallevand, Andrea (Medical science educator, 2019)
Purpose To investigate whether starting the clerkship year in family medicine (FM), internal medicine (IM), pediatrics, or surgery influences NBME shelf and USMLE Step 2 CK examination performance. Methods USMLE Step 1, Step 2 CK, and shelf examination scores for FM, IM, pediatrics, and surgery were collected. Sequences were selected on the following assignment criteria: rotation 1 (either FM or IM), rotation 5 (pediatrics), rotation 8 (surgery), rotation 1 (either pediatrics or surgery), and rotation 8 (IM). Multivariate analysis of covariance, with Step 1 as the covariate, was used to investigate rotation sequence on examination performance. Results Wilks’s statistic found no statistically significant effect of rotation sequence (starting the clerkship year in FM or IM) on the pediatrics, surgery, and Step 2 CK examinations ( Λ = .95, F [3,51] = .93, p ≤ .432). Wilk’s statistic for the covariate (Step 1) was statistically significant ( Λ = .488, F [3,51] = 17.827, p ≤ .001), indicating the two groups differ on Step 1 performance. Wilk’s statistic found no statistically significant effect of rotation sequence (starting the clerkship year in pediatrics or surgery) on the IM and Step 2 CK results ( Λ = .925, F [2,75] = 3.036, p ≤ .054). Wilk’s statistic for the covariate (Step 1) was statistically significant ( Λ = .309, F [2,75] = 83.915, p ≤ .001) indicating that the two groups differ on Step 1 performance. Conclusion Starting the clerkship year in FM, IM, pediatrics, or surgery does not influence subsequent performance on shelf examinations or on Step 2 CK.